Faktor-Faktor Yang Mempengaruhi Price Earning Ratio Saham Lq45 Di Indonesia - Taruna dan Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to analyze factors that influence price earning ratio of  LQ45 index  in Indonesia for the year 2013-2016. Sample was collected by using purposive sampling method. Based on the type of data and analysis, this research is called quantitative research and data used is secondary data. The results of this study indicate that dividend payout ratio and price book value affected the price earning ratio of LQ45, while return on equity, earnings per share growth and financial leverage have no effect on PER of LQ45 stock. Simultaneously, all the independent variables significantly influence the PER stock of LQ45. Based on the coefficient of determination can be concluded that all the independent variables affect the price earning ratio of LQ45 stock by 25.46%.